2000
DOI: 10.1002/1097-4628(20000929)77:14<3107::aid-app120>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of maleic anhydride-modified iPP studied by POM

Abstract: Melt nucleation and crystallization behavior of homo‐isotatic polypropylene (homo‐iPP), maleic anhydride (MAH)‐grafted‐iPP, and MAH‐modified iPP, produced from iPP and a small amount of MAH‐grafted‐iPP, was investigated by polarizing optical microscopy (POM), at Tc = 121–135oC. Nucleation processes at a given Tc were faster for modified PP as compared to neat iPP. The induction time for nucleation increased nonlinearly with increasing Tc and decreased for modified PP, probably as a result of promoted heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The morphology of iPP crystallized from the melt has been studied extensively over the past few decades using PLM [45][46][47], transmission electron microscopy (TEM), scanning electron microscopy (SEM) and atomic force microscopy (AFM) [48]. From investigation carried out by polarizing microscopy, dynamically and isothermally, on the analysis of nucleation morphology of iPP, a lot of information concerning the induction period, nucleation density, growth-rate of the spherulites, and distribution of the dimension of the spherulites can be obtained (Fig.…”
Section: Morphological Scales In Ippmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of iPP crystallized from the melt has been studied extensively over the past few decades using PLM [45][46][47], transmission electron microscopy (TEM), scanning electron microscopy (SEM) and atomic force microscopy (AFM) [48]. From investigation carried out by polarizing microscopy, dynamically and isothermally, on the analysis of nucleation morphology of iPP, a lot of information concerning the induction period, nucleation density, growth-rate of the spherulites, and distribution of the dimension of the spherulites can be obtained (Fig.…”
Section: Morphological Scales In Ippmentioning
confidence: 99%
“…Results showed that iPP could crystallize in a wide range of spherulite dimensions (from 10-50 μm to 280-370 μm) depending on the temperature of crystallization and crystallization conditions as well as the presence of nucleating agents [45][46][47][50][51][52]. The presence of maleic grafted PP (PP-g-MA) used as a modifier for PP split films leads to alteration of the crystallization kinetics, although a spherulitic morphology similar to neat PP was developed [45].…”
Section: Morphological Scales In Ippmentioning
confidence: 99%
“…Isotactic PP has been studied extensively for its polymorphic characteristics and crystallization behavior since 1960s [9] and the results of these studies are reported in many monographic [see, for instance summarized Ref. 10 and 11] and journal publications [12][13][14][15][16][17][18][19]. Its crystalline morphology influences greatly the overall polymer properties (rheological, physical and mechanical) and the properties of the final products made of PP.…”
Section: Synthesismentioning
confidence: 99%
“…The melting temperature of the β-form lamellae is near 152 to 164 o C, while the melting of the α-form lamellae occurs above 164 o C. Moreover, the α-form lamellae can still grow in the temperature range from 152 to 164 o C. iPP can crystallize in a wide range of spherulite dimensions (from 10-50 μm to 280-370 μm) depending on the temperature of crystallization and crystallization conditions as well as the presence of nucleating agents [35][36][37]. The presence of maleic grafted PP (PP-g-MA), most often used as an adhesion modifier for PP composite applications, leads to alteration of the crystallization kinetics, without any significant changes in polymer spherulitic morphology ( Figure 2) [16]. Selective nucleating agents are sometimes added to PP, before or during processing, to induce appearance of a certain polymorphic modification, to enhance the crystallization, to obtain more uniform morphology and to alter its mechanical properties or transparency.…”
Section: Synthesismentioning
confidence: 99%
“…So, different methods of chemical modification of PPs are developed to improve compatibility with and the adhesion to the reinforcing fibers. The grafting of different monomers, such as acrylic and methacrylic acids, acrylamide, ethylene glycol methacrylate as well as maleic anhydride (MAH), offers improved adhesion to numerous filler and decreased critical tension, introducing polar functional groups into the polymer backbone without affecting the basic properties of the polymer [21][22][23].…”
Section: Introductionmentioning
confidence: 99%